Floating Gas to Power (FGTP) Plants: Proposed Policy Framework for Nigeria - Mogbo, O.C.; Joel, O. F.; Ikiensikimama, S.S. (Scientific Research, 2020)
Floating Gas to Power (FGTP) has been identified as a frontier concept for stranded gas field development. Instead of exporting gas onshore, the gas is used offshore for generating electricity as an end product. Offshore to Onshore electric power transmission is usually by marine or subsea cabling. The electricity is eventually distributed into a large utility power grid. Recent literature has showed the potential economic viability of the FGTP option in the Offshore Nigeria space, whilst demonstrating that FGTP viability will be strongly impacted by levers controlled by Nigerian government policy. The main objective of this paper was to broadly identify, evaluate and recommend the necessary government policy directions which would allow FGTP projects to contribute to macroeconomic growth through valorization of hitherto stranded gas resources offshore Nigeria. The paper examined the Nigerian Gas Master Plan, the Power Master plan and the Petroleum Investment Bill (PIB), amongst other extant government policies and regulations to clarify the extent to which the policies and frameworks may have to be amended in order to accommodate the FGTP within the range of gas monetization options recognized in the Nigerian gas and Power policy space. The study surmises that the implementation of FGTP as an economically viable investment option offshore Nigeria would necessitate deliberate legislation, as well as economic ring fencing with a sufficiently strong legal and policy framework. Such measures would support the growth of the nascent gas monetization option as well as strengthen foreign investor confidence in the longevity of policy formulations pertaining to FGTP offshore Nigeria. Regarding the power industry element: It was also found that the sustainable offtake of FGTP generated electricity strongly depends on the formation and implementation of National Power policies will allow a robust and modern national power grid to function, and allow for efficient and effective recovery of investor’s funds. Finally, this work highlights the attractiveness of the FGTP option in the Offshore Nigeria space: it could prove an economical and environmentally friendly option for simultaneously solving the energy generation and monetization of stranded gas reserves challenges. If properly harnessed, it could potentially generate huge revenue for the government, resolve the epileptic power supply problem in Nigeria and create numerous employment opportunities.
International Journal of Engineering Science Invention (IJESI) Volume 9 Issue 12 Series I
Keywords: STEM; University of Port Harcourt; Gas to Power; Electricity; FGTP; Nigeria; Offshore; Policy